Peran Entrepreneurial Marketing dalam Memediasi Kompetensi Sumber Daya Manusia dan Inovasi untuk mencapai Keunggulan Kompetitif - Subagyo, Subagyo; Ernestivita , Gesty; Suhendra, Eupharasia Susy (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This study aims to determine the effect of HR competence and innovation on competitive advantage with entrepreneurial marketing as an intervening variable in the Food and Beverage Industry in East Java. This research is a quantitative research. The sample was determined as many as 100 entrepreneurs by purposing sampling technique. The data obtained from the questionnaire was then analyzed using SEM with the Smart PLS application tool. The results showed that the competence of HR and entrepreneurial marketing partially had a significant positive effect on competitive advantage, while innovation had no significant effect on competitive advantage. HR competence and innovation significantly affect entrepreneurial marketing. Likewise, it is proven that entrepreneurial marketing is proven to be able to mediate HR competencies and innovation to competitive advantage.